Oxidized Chitosan-Tobramycin (OCS-TOB) Submicro-Fibers for Biomedical Applications - Zhen Li; Shunqi Mei; Yajie Dong; Fenghua She; Chengpeng Li; Yongzhen Li; Lingxue Kong (Pharmaceutics, 2022)
Chitosan (CS) is a biodegradable, biocompatible, and non-toxic natural amino-poly-saccharide with antibacterial ability, owing to its positively charged amino groups. However, the low charge density leads to poor antibacterial efficiency which cannot meet the biomedical application requirements. In this study, Tobramycin (TOB) was grafted onto the backbone of oxidized chitosan (OCS) to synthesize oxidized chitosan-tobramycin (OCS-TOB). FTIR, 1H NMR and elemental analysis results demonstrated that OCS-TOB was successfully synthesized. OCS-TOB/PEO composite fibrous materials were produced by a self-made centrifugal spinning machine. In vitro experiments showed that cells proliferated on the submicro-fibrous OCS-TOB/PEO of appropriate concentration, and the antibacterial ability of OCS-TOB was much improved, compared with pristine CS. The results demonstrated that OCS-TOB/PEO nanofibrous materials could potentially be used for biomedical applications.